Improving Survival in Patients Treated for a Lung Cancer Using Self-Evaluated Symptoms Reported Through a Web Application. (October 2017) - Denis, Fabrice; Yossi, Senna; Septans, Anne-Lise; Charron, Alexandre; Voog, Eric; Dupuis, Olivier; Ganem, Gérard; Pointreau, Yoann; Letellier, Christophe
Abstract : Objectives: We retrospectively compared survivals in patients with a lung cancer history and followed by the so-called sentinel Web-application that allows early detection of relapse and early palliative care initiation versus a conventional follow-up in our center. Methods: The survival in 98 consecutive patients with lung cancer was assessed. The first part of them (the control arm) was retrospectively recruited between March 2011 and August 2012. The second half of them (the experimental arm) was prospectively recruited between August 2012 and December 2013 to weekly fill a form of 11 self-assessed symptoms, then processed by the "sentinel" Web-application. Data were sent to this sentinel application in real-time between planned visits. An email alert was sent to the oncologist when self-scored symptoms matched some predefined criteria. Follow-up visit and imaging were then organized after a phone call for confirming the suspect symptoms. In the control arm (49 patients), a common follow-up was applied (visit and imaging every 2 to 6 mo according to stage of tumor and kind of treatment). Results: Median follow-up duration was 12.3 months in the experimental arm and 16.7 months in the control arm ( P =0.27). Survival was significantly better in the sentinel arm than in the control arm ( P =0.0014). Median survival was 16.7 months in the control arm and 22.4 months in the experimental arm. One-year survival was 86.6% in the experimental arm and 59.1% in the control arm. Conclusions: Survival may be improved by early detection of relapse and early palliative care initiation by using sentinel-like Web-application.